Measurement of effective diffusion coefficients in dairy powders by confocal microscopy and sorption kinetic profiles. (April 2019) - Maidannyk, Valentyn; Lutjes, Eva; Montgomery, Sharon; McCarthy, Noel; Auty, Mark A.E.
Graphical abstract: Highlights: We present a new confocal microscopy based method for monitoring hydration of individual spray dried powder particles in real time. The new microscopy based technique could be used to measure effective diffusivity and correlated with moisture vapour uptake. Microscopy results indicate that hydration rate depends on the size of particle. Abstract: A new method for the visualisation and determination of local diffusion coefficients in dairy powders is described based on real-time visualisation of penetration of fluorescent dyes into individual particles of spray-dried dairy powders including skim milk powder, milk protein concentrate and whey protein isolate. The rehydration process was controlled by adding polyethylene glycol (PEG) as a viscosity modifier to the aqueous phase in ratios of 1:0, 1:1, 1:3 and 1:4 aqueous rhodamine to PEG, respectively. Real-time effective diffusivity values were obtained from analysis of confocal laser scanning microscope images. Particle size was measured optically. Results indicated that for all dairy powders, rehydration rates were highly dependent on particle size. Effective diffusivity increased linearly with increasing particle size and average effective diffusivity of the liquid phase was calculated for all particle size distributions using this dependence. The Guggenheim-Anderson-de Boer (GAB) water sorption relationship was used to model water sorption isotherms over a broad range of water activities. Vapour phase systems had significantly higher effective diffusivity than liquid phase systems. The results obtained by this new method is broadly in agreement with previously published works, suggesting this new method may be used to measure the hydration of individual powder particles.